2010
DOI: 10.1166/jnn.2010.2830
|View full text |Cite
|
Sign up to set email alerts
|

Differential Internalization of Superparamagnetic Iron Oxide Nanoparticles in Different Types of Cells

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) have attracted great attention for nanomedical applications, but the mechanisms underlying the transmembrane transport of SPION in variant cells has not been fully defined. The present study investigated the internalization of SPION in three cell models with different phagocytic capacity using transmission electron microscopy (TEM) and energy dispersive spectrometer (EDS) analyses. The EDS study aimed to further confirm if the suspected internalized particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Between each cell line, the 3T3 cells exhibited the highest fluorescence intensity at each time point. This result suggests that the membrane composition of the 3T3 cells is more permeable to the particles [33].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Between each cell line, the 3T3 cells exhibited the highest fluorescence intensity at each time point. This result suggests that the membrane composition of the 3T3 cells is more permeable to the particles [33].…”
Section: Resultsmentioning
confidence: 86%
“…In this study, we introduce 3T3 mouse fibroblasts and the human HeLa cervical cancer cell line. Care was taken to choose three unique cell lines that were known to exhibit differences in phenotype, cell division times, and endocytotic uptake [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of I K and I K1 channels by MWCNTs [9] may also rationally contribute to APD prolongation in cardiomyocytes if confirmed. Second, we showed that MWCNTs need to enter the cell to affect the I to channel, while the endocytotic process for nanomaterials entering cells with low phagocytotic capacity usually takes an hour or longer [34]. However, MWCNTs intravenous infusion soon (within minutes) induced bradyarrhythmias.…”
Section: Discussionmentioning
confidence: 94%
“…The NPs can be efficiently internalized by a variety of cell types through a combination of uptake routes, including, but not limited to, clathrin-mediated endocytosis (CME), caveolar endocytosis, macropinocytosis and, in specialized cells, phagocytosis (Ivanov 2008;Sahay, Alakhova, and Kabanov 2010;Gu et al 2011;Zhao et al 2011;Kafshgari, Harding, and Voelcker 2015). In macrophage cells multiple endocytotic mechanisms have previously been found responsible for the internalization of SPIONs, including CME, caveolae dependent mechanisms, macropinocytosis and phagocytosis (Raynal et al 2004;Xu et al 2010;Gu et al 2011;Lunov et al 2011;Schlorf et al 2010;Yang et al 2011). The internalization of SPIONs into macrophage models has been widely studied compared to non-macrophage cell types.…”
Section: Discussionmentioning
confidence: 99%